To be Fussed Over: A Critical Phenomenological Examination of Black Feminist Practices of Care in the Midst of Polycrisis. - Mali Mason, Qrescent (Paragraph, 2025)
This essay maps four Black feminist phenomenological reflections on care in the midst of polycrises. Linking the author's series of Instagram stories '#MyBlackFeministCaronaChronicles'; an edited collection of West Philadelphia responses to the COVID-19 pandemic and uprisings, How We Stay Free; Toni Cade Bambara's 1980 novel, The Salt Eaters; and bell hooks's 1994 Sisters of the Yam: Black Women and Self-Recovery, the author seeks to describe how Black feminist modes of care are depicted via a Black feminist critical phenomenology that sees care as linked to intersubjectivity, intersectionality and liberation.